Structural and Constructive Analysis of a Faux Vault, the Dome of San Juan de Dios Church, in Granada (SPAIN). Issue 5 (4th May 2021) - Suárez, F. J.; Bravo, R.; González, J. A.
ABSTRACT: The Basilica of San Juan de Dios in Granada designed by José de Bada y Navajas was built between 1734 and 1757. The complexity and dynamism of its architectural form make it as one of the greatest work of the Spanish Baroque. This paper presents an architectural and a constructive analysis of the dome over the transept of the basilica built according to the model of encamonada dome divulged by Fray Lorenzo de San Nicolás, additionally, this paper includes a review of similar domes. A structural analysis based on the Discrete Element Method (DEM) of the timbrel dome for static and dynamic loads is presented. The DEM is a numerical tool suitable to evaluate the mechanical behaviour of structures composed by a relatively high number of bricks. Therefore, it is a good candidate to analyse the dome exposed in this paper.